Osteogenic potential of a 3D printed silver nanoparticle-based electroactive scaffold for bone tissue engineering using human Wharton's jelly mesenchymal stem cells - Mira, Mira (2024)
This study aims to perform biological assessments of an electroactive and anti-infection scaffold based on polycaprolactone/0.5 wt% silver nanoparticles (PCL/AgNPs) that was fabricated using a green synthesis approach followed by a 3D printing method without utilization of any toxic solvents, which has not been explored previously. For this purpose, human Wharton's jelly mesenchymal stem cells (hWJ-MSCs) were used as a cell source to explore the biocompatibility and the ability to induce the osteogenesis process on the fabricated PCL and PCL/AgNPs scaffolds. Scanning electron microscopy (SEM), confocal microscopy and an alamar blue assay up to day 14 revealed that the PCL/AgNPs scaffolds have better cell attachment, penetration and proliferation than the PCL scaffolds. A gene expression study up to day 21 using the reverse transcription-quantitative polymerase chain reaction (RT-qPCR) showed that the PCL/AgNPs scaffolds have better osteogenic differentiation at the gene level than the PCL scaffolds. This is indicated by the 2-3 fold greater expression of runt-related transcription factor 2 (RUNX2), collagen type I alpha 1 chain (COL1A1), and osteopontin (OPN) than the PCL scaffold. A protein expression study up to day 21 using immunocytochemistry and detection of alkaline phosphatase (ALP) revealed that the PCL/AgNPs scaffolds have better osteogenic differentiation at the protein level than the PCL scaffolds. This is shown by the observed collagen type I and osteopontin protein, and ALP activity at day 21 of PCL/AgNPs scaffolds (768 U L−1) which is 1.3 times higher than that of the PCL scaffolds (578 U L−1). These biological assessments showed that the combination of a green synthesis approach to prepare AgNPs and solvent-free 3D printing methods to fabricate the PCL/AgNPs scaffolds led to better biocompatibility and ability to induce the osteogenesis process, which is attractive for bone tissue engineering and regenerative medicine applications.